2016
DOI: 10.1158/1078-0432.ccr-15-1181
|View full text |Cite
|
Sign up to set email alerts
|

CD73 Expression Is an Independent Prognostic Factor in Prostate Cancer

Abstract: Purpose: CD73 is an adenosine-generating ecto-enzyme that suppresses antitumor immunity in mouse models of cancer, including prostate cancer. Although high levels of CD73 are associated with poor prognosis in various types of cancer, the clinical impact of CD73 in prostate cancer remains unclear.Experimental Design: We evaluated the prognostic value of CD73 protein expression and CD8 þ cell density in 285 cases of prostate cancer on tissue microarray (TMA). Normal adjacent and tumor tissues were evaluated in d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
130
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 173 publications
(143 citation statements)
references
References 48 publications
4
130
2
1
Order By: Relevance
“…High ADORA2B expression is associated with worse patient outcome CD73-adenosine signaling pathway has been implicated in promoting tumor growth and metastases (1,2,(25)(26)(27). We have previously shown that high CD73 expression is associated with a poor prognosis in the primary TNBC subtype, and its overexpression in these tumors predicted chemoresistance to doxorubicin therapy (26).…”
Section: Resultsmentioning
confidence: 99%
“…High ADORA2B expression is associated with worse patient outcome CD73-adenosine signaling pathway has been implicated in promoting tumor growth and metastases (1,2,(25)(26)(27). We have previously shown that high CD73 expression is associated with a poor prognosis in the primary TNBC subtype, and its overexpression in these tumors predicted chemoresistance to doxorubicin therapy (26).…”
Section: Resultsmentioning
confidence: 99%
“…Although the association between CD73/CD39 expression and patient prognosis is complex (39), in many cases the expression of CD73 has been shown to negatively correlate with patient survival. This includes patient cohorts in breast (20), ovarian (22), renal cell (40), rectal adenocarcinoma (41), and prostate cancer (42). Furthermore, targeting this pathway has been shown to enhance clinical responses to chemotherapy (20) and other classes of immunotherapy (33,43,44).…”
Section: Genetic Targeting Of a 2a R Protects Car T Cells From Adenosmentioning
confidence: 99%
“…CD73 is expressed on both tumor cells and host immunosuppressive cells such as Tregs and myeloid-derived suppressor cells (MDSCs). CD73 expression has been shown to negatively correlate with patient prognosis in a number of cancer types (20)(21)(22), highlighting the relevance of the CD73/adenosine immunosuppressive axis in patients. Furthermore, preclinical studies have shown that targeting of either CD73…”
Section: Introductionmentioning
confidence: 99%
“…[42][43][44][45][46] CD73-deficient mice are resistant to tumor and show an increased influx of CD8 + T cells [44] and low number of Tregs within the tumor. [47] The expression of CD73 on various tumor cells from cancer patients, including breast, [46] glioblastoma, [48] prostate, [49] ovarian, [50] leukemia [51] has been associated with poor prognosis. Notably, some chemotherapeutics are able to increase the expression of CD73 on cancer cells, which may in turn represent a putative mechanism of resistance to chemotherapeutics.…”
Section: Critical Roles Of Adenosine In Tumor Progressionmentioning
confidence: 99%
“…Notably, some chemotherapeutics are able to increase the expression of CD73 on cancer cells, which may in turn represent a putative mechanism of resistance to chemotherapeutics. [46,49,51] On the other hand, targeting CD73 can improve the therapeutic potential of some conventional cancer treatments, including chemotherapy, radiotherapy and immunotherapy. For example, inhibition of CD73 in combination with doxorubicin prolonged the survival of mice with metastatic breast cancer.…”
Section: Critical Roles Of Adenosine In Tumor Progressionmentioning
confidence: 99%